Diagnostic purposes of education: Problems, strategies and solutions - А. P. Usol’tsev; Т. N. Shamalo; Е. P. Аntipovа (Образование и наука)
Introduction. A diagnostic educational purpose is an essential condition for successful realisation of any pedagogical technology, but all attempts to introduce general diagnostic purposes in the education system have failed: practically always, it is not the essential new features but the formal indicators, which become the actual target. The current article analyses the phenomenon of “degradation of the educational purpose” and actualises the question of the feasibility of efforts to achieve diagnostic evaluation of education quality. The main strategies for creating diagnostic purposes of education are considered. A forecast of further development of this process in the context of global digitalisation is proposed, which fundamentally transforms not only the procedures, but also the essence of diagnostics of educational results.The aim of the present research is to discuss the problem of diagnostic purposes setting in education and possible ways to solve it.Methodology and research methods. The research methodology is based on the principles of synergy. The theoretical methods include the analysis of publications, normative documents, and programmes for teaching in secondary and higherlevel education. The empirical data have been obtained through the questionnaire for school teachers and university educators, as well as through the authors’ personal experience. The survey received responses from 102 school physics teachers mainly from Ekaterinburg and theSverdlovsk region, and 131 high school physics teachers from 8 pedagogical universities and theUralFederalUniversity.Results and scientific novelty. The study provides the examples of diagnostic purpose degradation on the level of national education system, which manifests itself in rerouting the activity towards the achievement of formal outcome indicators. The diagnostic purpose deformation is caused by dividing the functions between those who control education and those who perform it – teachers. As a result of this division, the teachers lose their subjectivity.The key factors, which fundamentally limit the significance of diagnostic educational purposes, are highlighted. The authors propose the ways of avoiding negative side effects in the case of implementation of these goals. The potential boundaries, for which it is not advisable to spread the requirement to set diagnostic goals, are indicated.The authors consider two strategies applied for formulation of diagnostic purposes. The first one consists in the formulation of a great number of partial diagnostic purposes, the second one – in the formulation of one general purpose. It is demonstrated that none of the strategies leads to the desired outcome, and that the formally evaluated education quality is not associated with the life experience of a person and with the economic growth of the state.The possible solution is to give up the attempt to formulate one holistic diagnostic procedure of evaluation of the mythical education quality; to specify consistent requirements exceptionally applicable to the creation of favourable conditions for the education members, e.g. the technology of educational “digital doubles” to optimise education strategies aimed at providing each pupil with a chance to live a successful life.Practical significance. The authors’ assessments and conclusions create methodological prerequisites for unfolding a discussion about the role of diagnostic educational purposes and the feasibility of their monitoring. The proposals to solve the problem will be useful in the process of development of Federal State Educational Standards, curricula and learning programmes at all levels of education.The authors hope that the conclusions drawn may stimulate researchers and education administrators to focus their activity on the creation of an enabling environment for the education members and not on constructing the “Procrustean bed” for education in the form of diagnostic purposes disconnected from reality.